2016
DOI: 10.1128/jvi.02651-15
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose, an mTOR-Independent Inducer of Autophagy, Inhibits Human Cytomegalovirus Infection in Multiple Cell Types

Abstract: Human cytomegalovirus (HCMV) is the major viral cause of birth defects and a serious problem in immunocompromised individuals and has been associated with atherosclerosis. Previous studies have shown that the induction of autophagy can inhibit the replication of several different types of DNA and RNA viruses. The goal of the work presented here was to determine whether constitutive activation of autophagy would also block replication of HCMV. Most prior studies have used agents that induce autophagy via inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 70 publications
(95 reference statements)
4
54
1
Order By: Relevance
“…6A, bottom row), both nestin and ␤-tubulin III were present, indicating a progression in differentiation to postmitotic neurons; however, projections were not as frequent as in the mock-infected controls and were often aberrant in appearance. Several studies done in two-dimensional (2D) culture systems reported the inability of infected NPCs to properly differentiate down a neural pathway (27,31,32,34) and that infected neurons had defective neurite outgrowth (31,56) and degeneration of ␤-tubulin III signal integrity in their processes (31,56). Our studies substantiate these findings.…”
Section: Discussionsupporting
confidence: 87%
“…6A, bottom row), both nestin and ␤-tubulin III were present, indicating a progression in differentiation to postmitotic neurons; however, projections were not as frequent as in the mock-infected controls and were often aberrant in appearance. Several studies done in two-dimensional (2D) culture systems reported the inability of infected NPCs to properly differentiate down a neural pathway (27,31,32,34) and that infected neurons had defective neurite outgrowth (31,56) and degeneration of ␤-tubulin III signal integrity in their processes (31,56). Our studies substantiate these findings.…”
Section: Discussionsupporting
confidence: 87%
“…However, autophagy can also be regulated by various pathways independent of mTOR. [38][39][40][41] Uncoupling between mTOR and autophagy was found in our study. Our data suggest that increased autophagy activation and unchanged mTOR activation can coexist in keratocytes with intracellular SiNP accumulation.…”
Section: Discussionsupporting
confidence: 73%
“…However, recently, several reports indicated that mTOR pathway is not the only control mechanism of autophagy. Autophagy can be regulated by various pathways which are independent of mTOR, and this suggests that these two pathways (mTOR and autophagy) are not always coupled to each other46474849. The uncoupling of mTOR and autophagy was observed in our study.…”
Section: Discussionsupporting
confidence: 47%